Bioethics: history and addressing issues - Bołoz, Wojciech (Studia Ecologiae et Bioethicae, 2003)
Bioethics is a new scientific branch created over 30 years ago, connecting natural sciences (biology, medicine) with the science of morals in human conduct. (ethics). Bioethics started to grow in the area of ecology, therefore primarily it appeared as a discipline of environmental protection and preservation of the ecosystem (environmental ethics). Later the matter of dispute became limited to problems related to human health and its promotion (medical ethics). However, these problems are closely related to plant preservation and animal life protection. The practice in bioethics is faced with difficulties related to the interdisciplinary character of this branch and the axiological pluralism of the modern world. In consequence, in the area of bioethics most important become human being respect and human rights as touchstones universally accepted in social life practice and international law. A favorable fact is that the European Union has recognized and accepted these values as its own cultural identity constituents.